Analyzing environmental communication and citizen science in the context of environmental monitoring and assessment for Agenda 2030 in rural settings of Chile and Sweden - Alarcón-Ferrari, Cristián; Jönsson, Mari; Do, Thao; Gebrehiwot, Solomon Gebreyohannis; Chiwona-Karltun, Linley; Mark-Herbert, Cecilia; Powell, Neil; Ruete, Alejandro; Hilding-Rydevik, Tuija; Bishop, Kevin (Frontiers in Communication, 2024)
This article offers an analysis of environmental communication (EC) and citizen science (CS) in the context of Environmental Monitoring and Assessment (EMA) for the implementation of Sustainable Development Goal 15 (Life on Land) in Chile and Sweden. The paper is based on fieldwork in two rural study areas of Chile and Sweden where we followed different CS initiatives in relation to EMA and Agenda 2030. We conducted interviews, analyzed documentation and conducted an SDG mapping workshop to understand the implementation of SDG 15 in these two rural forest settings. Our findings suggest that CS has potential as a democratic innovation for environmental governance in both countries. However, we also found important barriers to the legitimacy of CS as a feature of EMA and local environmental governance in both countries. The paper situates CS in the wider governance and environmental communication processes in regional politics surrounding implementation of national policies for the use of natural resources. The article offers new insights into the barriers and possibilities for public participation in environmental governance and policy at local levels, by addressing the interlinkages between environmental communication and citizen science in rural settings.